Development of a multi-metric index based on macroinvertebrates for wetland ecosystem health assessment in predominantly agricultural landscapes, Upper Blue Nile basin, northwestern Ethiopia - Assefa, Workiyie Worie; Eneyew, Belachew Getnet; Wondie, Ayalew (Frontiers in Environmental Science, 2023)
Developing multi-metric indices (MMIs) as a tool for inland water ecosystem assessment has attracted the attention of the global scientific community. The number of studies, which developed macroinvertebrate-based multi-metric indices for wetlands, however, was very limited. Thus, more work is needed to refine and implement it depending on the ecological contexts of wetlands. On top of this, we developed multi-metric indices based on macroinvertebrate assemblages that could be used for the ecological health assessment of wetlands that are impacted by agricultural activities in North-western Ethiopia. About 20 sampling sites were established in four wetlands along the disturbance gradient to take water and macroinvertebrates samples. The reference sites, which were least disturbed by human intervention, were established for the construction of multi-metric indices. Six core metrics were selected for the development of the final multi-metric indices from fifty-six potential metrics of macroinvertebrate assemblages after passing through sensitivity and statistical tests. The findings demonstrated all reference sites had good or high ecological conditions. On the contrary, the ecological statuses of nearly 70% of the impaired sites were found to be in bad to poor conditions. A significant distinction between reference and impaired sites suggested our index ability to identify the gradient variation in the ecological condition of wetlands. A strong negative relationship of the multi-metric indices model with most of the physicochemical variables and all human disturbance factors also suggested the appropriateness of the developed index in informing the ecological status of wetlands. Thus, we believe that our multi-metric indices could be a useful biomonitoring tool for the assessment and monitoring of wetland ecological conditions in predominantly agricultural landscapes in the Upper Blue Nile basin and beyond.